Oyster farming control on phytoplankton bloom promoted by thermal discharge from a power plant in a eutrophic, semi-enclosed bay. (1st August 2019) - Jiang, Zhibing; Du, Ping; Liao, Yibo; Liu, Qiang; Chen, Quanzhen; Shou, Lu; Zeng, Jiangning; Chen, Jianfang
Abstract: Temperature increase caused by thermal discharge from power plants promotes phytoplankton growth and frequent bloom in eutrophic subtropical waters, particularly in cold seasons. Suspension filter-feeding bivalves show size-selective grazing on phytoplankton. Thus, we hypothesized that algal bloom under thermal stimulation could be controlled and that phytoplankton community was structured by oyster farming. Here, ten cruises were conducted in two oyster farms (OFs) and control areas (CAs) adjacent to the Ninghai Power Plant in the upper section of Xiangshan Bay during 2009–2015. We found that thermal discharge induced severe winter algal blooms. Phytoplankton abundance and chlorophyll a (chla) were significantly lower (46.3% and 28.3%, respectively) in OF than in CA, indicating a high filtration efficiency by oysters and the associated biofouling assemblages. In addition, oyster farming significantly increased species richness (by 26.3%), Shannon–Wiener diversity (by 38.3%), and Pielou's evenness indices (by 28.8%) and reduced suspended solids (by 12.2%), total organic carbon (by 18.4%), dissolved inorganic nitrogen (by 1.5%), and phosphorus (by 3.7%). Furthermore, oyster farming considerably reduced (increased) micro-chla contribution (pheophytin/chla) by 34.8% (71.1%), suggesting a strong size-selective grazing on phytoplankton. Analysis of similarity revealed a significant difference in phytoplankton community composition between OF and CA. However, after the removal of culture rafts, all the abundance, chla, species diversity, dominant species, size structure, and community composition of phytoplankton showed no significant difference. Our study demonstrated that oyster farming effectively alleviated eutrophication and algal bloom and enhanced phytoplankton diversity, which provides guidance for aquaculture and ecological restoration in subtropical coastal eutrophic waters. Graphical abstract: Image 1 Highlights: Thermal discharge induced severe winter algal blooms. Oyster farming effectively alleviated eutrophication and algal bloom. Oyster farming significantly increased phytoplankton diversity. Oyster farming reduced suspended solids and total organic carbon.